Socio-Cultural Strength: Optimization of Bhuppa’, Bhâbhu’, Ghuru, and Rato in Establishing Compliance in Madurese Familial Conduct - Susylawati, Eka; Hariyanto, Erie; Hosen, Hosen; Hamzah, Moh (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
The identification of the Madurese local concept, Bhuppa’-Bhâbhu’-Ghuru-Rato, is a part of the conflict resolution instrument based on social construction theory. This concept serves as a strong foundation underlying the social relationships and moral structure of the Madurese community, which remains deeply rooted in various aspects of daily life. This research aims to analyze the significant role of the socio-cultural value system of the Madurese community in shaping the behavioral compliance of Madurese families. The research is qualitative in nature, relying on both primary and secondary data. Primary data is obtained from field studies, including direct observations and mapping of research aspects. The research findings indicate that there has been controversy in the interpretation of threats related to social inequality, economic family issues, and the pandemic already experienced. This interpretational controversy has been caused by differences in understanding, conflicting interests, and varying traditions or practices. Differences in understanding are evident from the varying levels of comprehension between groups in the community, which also highlights differences in literacy levels when interpreting these issues. The four important elements of Bhuppa’-Bhâbhu’-Ghuru-Rato play a vital role in controlling and providing guidance through families to enhance compliance. These elements are actualized in daily praxis as binding normative rules.